Suitability of IgG responses to multiple Plasmodium falciparum antigens as markers of transmission intensity and pattern - Kyei-Baafour, Eric (PLoS One, 2021)
Detection of antibody reactivity to appropriate, specific parasite antigens may constitute a sensitive and cost-effective alternative to current tools to monitor malaria transmission across different endemicity settings. This study aimed to determine the suitability of IgG responses to a number of P. falciparum antigens as markers of transmission intensity and pattern. Antibody responses to multiple malaria antigens were determined in 905 participants aged 1–12 years from three districts with low (Keta), medium (Hohoe) and high (Krachi) transmission intensity in the Volta region of Ghana. Blood film microscopy slides and dry blood spots (DBS) were obtained for parasitaemia detection and antibody measurement, respectively. Sera were eluted from DBS and levels of IgG specific for 10 malaria antigens determined by a multiplex assay. Results were compared within and among the districts. Total IgG responses to MSPDBL1, MSPDBL(Leucine), MSP2-(FC27), RAMA, and PfRh2a and PfRh2b were higher in Krachi than in Hohoe and Keta. Seroprevalence of IgG specific for MSPDBL(Leucine), RON4, and PfRh2b were also highest in Krachi. Responses to RALP-1, PfRh2a and PfRh2b were associated with patent but asymptomatic parasitaemia in Keta, while responses to MSPDBL1, MSPDBL(Leucine), MSP2-(FC27), RAMA, Rh2-(2030), and PfRh2b were associated with parasite carriage in Hohoe, but not in Krachi. Using ROC analysis, only PfRh2b was found to predict patent, but asymptomatic, parasitaemia in Keta and Hohoe. Antibody breadth correlated positively with age (r = 0.29, p<0.0001) and parasitaemia (β = 3.91; CI = 1.53 to 6.29), and medium to high transmission (p<0.0001). Our findings suggest differences in malaria-specific antibody responses across the three transmission zones and that PfRh2b has potential as a marker of malaria transmission intensity and pattern. This could have implications for malaria control programs and vaccine trials.